Mentoring for the Development of MSMEs in Menes District through the Making of Halal Certification - Indri Wisdiarti Anugraheni (Institute of Multidisciplinary Research and Community Service, 2024)
Abstract: One of the drivers of the economy in Indonesia today is the consistent increase in MSMEs locally and nationally. In running MSMEs, there is a need for proper development and management so that they are still able to develop and advance in their business. In every economic sector, MSMEs (micro, small and medium enterprises) are autonomous production sectors run by the private sector or legal entities. Since Indonesia is predominantly Muslim, it is necessary to ensure that the products sold by MSMEs are halal. This service aims to assist MSME players in obtaining halal certification to increase consumer confidence. The